(untitled) (Ornitología Colombiana, 2021)
A new species of Henicorhina wood-wren (Aves, Troglodytidae) is described from the Munchique massif of the Western Andes of Colombia. The Munchique Wood-Wren Henicorhina negreti is closely related to and probably derived from the Gray-breasted Wood-Wren Henicorhina leucophrys of Central and South America. Henicorhina negreti appears restricted to a narrow band of extremely wet, stunted cloud forest on the upper Pacific slope, characterized by nearly continuous fog, high epiphyte loads and frequent landslides; it is abruptly replaced in taller forest at lower elevations on this slope by H. l. brunneiceps, and on the drier east slope by H.l. leucophrys. The new species differs from adjacent forms of H. leucophrys in its distinctly barred abdomen, dark juvenal plumage, relatively short tail and longer tarsi. Its song is also very distinct, and the adjacent forms of H. leucophrys do not respond to it while they do to each others (despite the fact that the new species occurs between them). Conversely, the new species does not respond to songs of H. l. leucophrys or H. l. brunneiceps, strongly suggesting that it is reproductively isolated from them and has distinct habitat requirements. Similarities between the ecology of H. negreti and that of H. leucoptera, another restricted-range endemic sympatric but not syntopic with H. leucophrys, are discussed. Possible threats to H. negreti due to forest clearance and global climate change are discussed, and we suggest that the species be accorded Critically Endangered status.